Rom, Italien: Domus Aurea - Beste, Heinz-Jürgen (e-Forschungsberichte des DAI, 2023)
The most famous Neronian buildings are undoubtedly his palace complexes. All these efforts to create a “Neronian” architecture culminated in the Domus Aurea. Although these reports give a different impression, the Domus Aurea building project was in fact never quite finished. Still, it is plausible that an overall plan or a model of the Domus Aurea project existed, or that the courtiers gained a good impression of the intended look of the complex from the princeps’ comments about it. Because of later building activity, only a few of those structures in the area of the Domus Aurea, which “seemed like cities,” remain. Most of what has survived belonged to the part of the Domus Aurea which was located on the side of the Oppian Hill, believed to have been the main building of the complex. At present, however, the exact dimension of the building complex and the shape of its layout are not yet known.